Analysis of Intrapersonal Communication in Increasing Students' Emotional Intelligence - Kasrah, Rini; Yudhawati, Ine; Gotama, I Kadek Dwiki; Paramita, Jesy; Gautama, Sidartha Adi (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2024)
This research aims to analyze how intrapersonal communication plays a role in increasing students' emotional intelligence. Intrapersonal communication, which involves internal dialogue and understanding oneself, is considered an important element in the development of emotional intelligence. This research uses a qualitative research approach with a case study method carried out by conducting interviews and involving students at a private university. Data was collected through in-depth interviews which were used to collect data from informants selected purposively, namely students from 3 study programs at this private university, observations were also carried out to obtain information regarding communication carried out and interactions between students, and questionnaires to collect data and analyze complex phenomena in appropriate contexts. The research results show that students who have good intrapersonal communication skills tend to have higher emotional intelligence, which is reflected in their ability to manage emotions, empathize, and build positive intrapersonal relationships.